Preparation method of silane coupling agent modified carbon aerogel / silicone rubber dual-network composite material and obtained product

By modifying carbon aerogel with silane coupling agent and combining it with silicone rubber to form a dual-network composite material, the problem of balancing conductivity and mechanical properties is solved, achieving high strain sensitivity and stable resistance response, thus expanding its application in the field of strain sensing.

CN119264671AActive Publication Date: 2025-01-07SHANDONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411418558.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the preparation process of existing conductive silicone rubber, the use of carbon-based fillers makes it difficult to achieve both conductivity and mechanical properties. The insufficient compatibility between carbon aerogel and silicone rubber network limits its application in the field of strain sensing.

Method used

A silane coupling agent-modified carbon aerogel was combined with silicone rubber, and the modified carbon aerogel was combined with a silicone rubber raw material solution through a vacuum-assisted impregnation process to form a silane coupling agent-modified carbon aerogel/silicone rubber dual-network composite material.

Benefits of technology

Excellent electrical conductivity and high tensile strength are achieved with low conductive filler content, improving strain sensitivity and resistance response stability, and enhancing the compatibility between carbon aerogel and silicone rubber network.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264671A_ABST
    Figure CN119264671A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silane coupling agent modified carbon aerogel / silicone rubber dual-network composite material and an obtained product, a silane coupling agent is adopted to modify carbon aerogel, then a silicone rubber raw material solution is filled into the obtained modified carbon aerogel through a vacuum-assisted impregnation method, and then vacuum curing molding is performed to obtain the silane coupling agent modified carbon aerogel / silicone rubber dual-network composite material. The silane coupling agent modified carbon aerogel / silicone rubber dual-network composite material is obtained. By virtue of the characteristics of high porosity, large specific surface area, high conductivity and low density of the carbon aerogel, the composite material can realize relatively excellent conductivity under the condition of extremely small addition amount of the conductive filler; and the matching compatibility of a carbon aerogel network and a silicone rubber network is effectively improved through a method of surface modification and silicone rubber formula optimization, so that ultrahigh and adjustable strain sensitivity, capacity of capturing micro strain (0.1%) and excellent resistance response stability are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a silane coupling agent modified carbon aerogel / silicone rubber double network composite material, and also relates to a silane coupling agent modified carbon aerogel / silicone rubber double network composite material, belonging to the technical field of conductive silicone rubber materials. Background Art

[0002] Conductive silicone rubber is an important conductive polymer material. It retains the excellent properties of silicone rubber such as easy processing, high resilience and weather resistance. At the same time, its conductive properties can be adjusted by adjusting the type and amount of conductive fillers. Generally, the fillers used in conductive silicone rubber can be divided into two categories: metal fillers (such as copper powder and silver powder); carbon fillers (such as conductive carbon black, carbon fiber, carbon nanotubes, and graphene). Among them, metal fillers are superior to carbon fillers in terms of conductivity, but their compatibility with silicone rubber is very poor and their salt spray resistance is insufficient, resulting in a decrease in the comprehensive performance of conductive silicone rubber and a limited scope of application. On the contrary, although the conductivity of carbon fillers is relatively weak, they have excellent reinforcement properties for silicone rubber and good compatibility. They can simultaneously improve the electrical and mechanical properties of silicone rubber to meet the more stringent requirements of silicone rubber in high-end manufacturing fields such as aerospace, electronics and electrical. However, in the traditional preparation process, carbon-filled conductive silicone rubber needs to add a large amount of conductive fillers to achieve good conductivity. However, the addition of a large amount of conductive fillers destroys the original structure of silicone rubber, and the uneven dispersion of a large amount of fillers will seriously affect the mechanical properties of silicone rubber, causing the overall performance to decline. These are the problems and shortcomings in the current scientific research of conductive silicone rubber. Therefore, in order to make silicone rubber achieve excellent electrical and mechanical properties, it is necessary to build a continuous and matching conductive network in the silicone rubber network with a low amount of conductive fillers. Therefore, the process of successfully introducing a continuous conductive network in silicone rubber and matching the two networks is particularly important in the preparation process of conductive silicone rubber. At present, there are few studies in this area, and researchers have not proposed a suitable conductive silicone rubber preparation process for this problem.

[0003] In recent years, with the in-depth study of the construction of three-dimensional conductive network structure of silicone rubber, the conductive carbon aerogel structure has also attracted the attention of many researchers. Carbon aerogel has the characteristics of high porosity, large specific surface area, high conductivity, good chemical inertness, and low density. It is very suitable for embedding into the silicone rubber network as a conductive network to obtain a double-network conductive silicone rubber with good comprehensive performance. However, there are few related studies on the modification of carbon aerogel according to the characteristics of silicone rubber. For the silicone rubber system, most research teams have used more mature polysiloxane products on the market, and have not designed silicone rubber formulas that match the characteristics of the carbon aerogel conductive network. The above two problems will affect the matching compatibility between the carbon aerogel conductive network and the silicone rubber network, and then affect the comprehensive performance of the conductive silicone rubber, and ultimately limit its application in the field of strain sensing. Therefore, this type of double-network conductive silicone rubber currently needs to be further optimized.

[0004] The Chinese invention patent with the patent publication number CN115010964A discloses a method for preparing conductive silicone rubber. The specific preparation method is as follows: a conductive filler is mixed with n-heptane to obtain a mixture A, wherein the conductive filler is a mixture of graphene, carbon nanotubes and carbon fiber materials; a liquid silicone rubber is mixed with n-heptane to obtain a mixture B; the mixture A and the mixture B are first mixed evenly in a desired proportion, and then vacuum treatment, pouring, and standing are performed in sequence until the n-heptane is completely volatilized, and then a conductive silicone rubber composite material is obtained by curing, wherein the mass ratio of the mixture A to the mixture B is 1:1-1.5, and the content of graphene in the conductive silicone rubber composite material is 4.5-5.5wt%, the content of carbon nanotubes is 1-1.25wt%, and the content of carbon fiber is 6-7.5wt%. The volume resistivity of the conductive silicone rubber composite material is 10Ω·cm, that is, the conductivity is 10S / m, as tested by the four-probe method. This patent uses a relatively large amount of conductive filler (11.5-14.25wt%) to achieve relatively excellent conductive properties, which will affect the mechanical properties of silicone rubber. Moreover, this patent does not involve research on the conductive network in the conductive silicone rubber composite material and its matching compatibility with the silicone rubber network. Summary of the invention

[0005] In view of the deficiencies mentioned in the prior art, the present invention provides a method for preparing a silane coupling agent modified carbon aerogel / silicone rubber double network composite material. The method comprises the following steps: using the modified carbon aerogel as a conductive filler, and using a vacuum-assisted infusion process to fill a silicone rubber raw material solution into the modified carbon aerogel, and then using a vacuum curing molding process to obtain the silane coupling agent modified carbon aerogel / silicone rubber double network composite material.

[0006] Specifically, the preparation method of the silane coupling agent modified carbon aerogel / silicone rubber double network composite material provided by the present invention comprises the following steps:

[0007] (1) Using carbon materials to prepare carbon aerogel;

[0008] (2) Surface modification of carbon aerogel using silane coupling agent;

[0009] (3) Using modified carbon aerogel as a conductive filler, a vacuum-assisted infusion process is used to fill the silicone rubber raw material solution into the modified carbon aerogel, and then a vacuum curing molding process is performed to obtain a silane coupling agent modified carbon aerogel / silicone rubber double network composite material.

[0010] Furthermore, the carbon material can be graphene oxide, carbon nanotubes, carbon fibers, cellulose, resorcinol, formaldehyde, melamine, phenol, furfural, cresol, etc., preferably graphene oxide.

[0011] Furthermore, the carbon aerogel can be prepared by a method reported in the prior art, such as a sol-gel method (Gao Q, Wang X, Shi Z, et al. Synthesis of porous NiCo2S4aerogel forsupercapacitor electrode and oxygen evolution reaction electrocatalyst [J]. Chemical engineering journal (Lausanne, Switzerland: 1996), 2018, 331: 185-193.), a hydrothermal method (Xu Y, Sheng K, Li C, et al. Self-Assembled Graphene Hydrogel via a One-Step Hydrothermal Process [J]. ACS nano, 2010, 4 (7): 4324-4330.), a chemical vapor deposition method (Chen Z, Ren W, Gao L, et al. Three-dimensional flexible and conductive interconnected graphene networks grown by chemical vapour deposition [J]. Nat Mater, 2011, 10 (6): 424-428.), a bubble template method (Pang ... K, Song X, Xu Z, et al. Hydroplastic foaming of graphene aerogels and artificially intelligent tactile sensors[J]. Sci Adv, 2020, 6(46).), ice template method (Huang C, Wang Y, Cheng Y, et al. Naturally dried superelastic bioinspired graphene aerogel for pressure / stretch sensing and separation[J]. Composites science and technology, 2022, 226: 109549.), etc., or a combination of two or more of these methods.

[0012] In a specific embodiment of the present invention, carbon aerogel is prepared by a method combining a bubble template method and an ice template method, which can be specifically referred to the method reported in the prior art (Zhang X, Zhang T, Wang Z, et al. Ultralight, Superelastic, and Fatigue-Resistant Graphene Aerogel Templated by GrapheneOxide Liquid Crystal Stabilized Air Bubbles[J]. ACS applied materials&interfaces, 2019, 11(1): 1303-1310.).

[0013] Furthermore, the modified carbon aerogel is obtained by modifying the carbon aerogel with a silane coupling agent, and the specific preparation method is: the carbon aerogel is soaked in a mixed solution of the silane coupling agent and an organic solvent, and then dried to obtain the modified carbon aerogel. The purpose of soaking is to allow the silane coupling agent to fully enter the carbon aerogel.

[0014] Furthermore, the carbon aerogel is first modified with a silane coupling agent and then compounded with silicone rubber, which optimizes the interface compatibility between the aerogel and the silicone rubber, thereby effectively improving the tensile strength of the composite material. The silane coupling agent can be vinyl triethoxysilane, vinyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane, aniline methyl triethoxysilane, etc., preferably vinyl triethoxysilane. The successful introduction of the silane coupling agent improves the crosslinking degree of the composite material.

[0015] Furthermore, in the mixture of the silane coupling agent and the organic solvent, the concentration of the silane coupling agent is 3-9wt%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%. The organic solvent can dissolve the silane coupling agent, and can be an alcohol solvent, such as methanol, ethanol, etc.

[0016] Furthermore, the soaking is carried out at room temperature, and the soaking time is generally 10-12 hours.

[0017] Furthermore, after soaking, the mixture is dried under normal pressure at a temperature of 55-65° C., such as 55° C., 56° C., 57° C., 58° C., 59° C., 60° C., 61° C., 62° C., 63° C., 64° C., 65° C., preferably 60° C. The drying time is generally 24-26 hours.

[0018] Furthermore, the vacuum-assisted infusion method is a common method for filling silicone rubber into conductive materials. The operation method is as follows: slowly pour the fully mixed silicone rubber raw material solution into a container containing modified carbon aerogel, so that the liquid level exceeds the upper surface of the aerogel by about 2mm, and adjust the position of the modified carbon aerogel in the silicone rubber raw material solution so that it is in the middle of the container. Place the container in a vacuum drying oven, and use the vacuum environment to assist the silicone rubber raw material solution to be fully infiltrated into the aerogel. During this period, it is necessary to unload the vacuum every 15 minutes, restore it to normal pressure, and then re-evacuate. Repeat this operation several times until the silicone rubber raw material solution no longer produces bubbles in the vacuum environment. The vacuum degree is generally 0.05-0.1Mpa, and it is completed when the silicone rubber raw material solution no longer produces bubbles in the vacuum environment.

[0019] Furthermore, the vacuum curing molding is also a commonly used method in the prior art, and its operation method is: after completing the vacuum-assisted infusion process, there is no need to take the sample out of the vacuum drying oven, and the vacuum drying oven is directly set to a specific temperature, so that it is cured under a vacuum environment, and finally a double-network conductive silicone rubber composite material is prepared. During vacuum curing molding, the vacuum degree is generally 0.05-0.1Mpa, and the temperature is generally 55-65°C, such as 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, preferably 60°C. The vacuum curing time is generally 12-18h, such as 12h, 13h, 14h, 15h, 16h, 17h, 18h.

[0020] Furthermore, the silicone rubber raw material solution is composed of: 100 parts by weight of vinyl-terminated polydimethylsiloxane, 0-50 parts of white carbon black, an appropriate amount of a crosslinking agent, 4-6 parts of polydimethylsiloxane, 0-50 parts of vinyl-terminated methyl silicone resin, 0.2-0.4 parts of an inhibitor, and 1.5-2 parts of a Pt catalyst.

[0021] Further, the vinyl-terminated polydimethylsiloxane is selected from one or both of a vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2200 mPa·s and a vinyl content of 0.0067-0.0135 mol / 100 g and a vinyl-terminated polydimethylsiloxane having a viscosity of 480-520 mPa·s and a vinyl content of 0.0141-0.0173 mol / 100 g, preferably a combination of the two. Wherein, the vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2200 mPa·s accounts for 0-35wt% of the total vinyl-terminated polydimethylsiloxane, such as 0%, 1%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 35%, preferably 1-35%, more preferably 10-35%.

[0022] Further, the amount of white carbon black is 0-50 parts, for example, 0 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts.

[0023] Furthermore, the viscosity of the polydimethylsiloxane is 480-520 mPa·s. The amount of the polydimethylsiloxane used is 4-6 parts, for example, 4 parts, 5 parts, or 6 parts.

[0024] Furthermore, the crosslinking agent is hydrogen-containing silicone oil with a hydrogen content of 0.6-1.0wt%. The amount of the crosslinking agent added is determined according to the standard that the molar ratio of carbon-carbon double bonds in vinyl-terminated polydimethylsiloxane and vinyl-terminated methyl silicone resin to silicon-hydrogen bonds in hydrogen-containing silicone oil is 1:1.1-1.3.

[0025] Furthermore, the vinyl content of the vinyl terminated methyl silicone resin is 0.03-0.05 mol / 100 g, the viscosity is 2300-2600 mPa·s, and the amount of the vinyl terminated methyl silicone resin is 0-50 parts, for example, 0 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts.

[0026] Furthermore, the inhibitor is an acetylene cyclohexanol solution with a concentration of 4-6 wt%, and the solvent is polydimethylsiloxane with a viscosity of 480-520 mPa·s.

[0027] Furthermore, the Pt catalyst is a platinum complex of tetramethyldivinylsiloxane.

[0028] Preferably, the silicone rubber raw material solution is composed of: 100 parts by weight of vinyl-terminated polydimethylsiloxane, 10-30 parts of white carbon black, an appropriate amount of a crosslinking agent, 5 parts of polydimethylsiloxane, 30 parts of vinyl-terminated methyl silicone resin, 0.3 parts of an inhibitor, and 1.5-1.7 parts of a Pt catalyst.

[0029] In a specific embodiment of the present invention, a preferred method for preparing a vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite material is provided, which specifically comprises the following steps: using reduced graphene oxide as a raw material, preparing a reduced graphene oxide aerogel network structure by a method combining a bubble template method and an ice template method, then soaking the reduced graphene oxide aerogel in an anhydrous ethanol solution of vinyl triethoxysilane, and then preparing a vinyl triethoxysilane modified reduced graphene oxide aerogel by normal pressure drying. Vinyl terminated polydimethylsiloxane, polydimethylsiloxane, white carbon black, a crosslinking agent, a vinyl terminated methyl silicone resin, an inhibitor and a Pt catalyst are uniformly mixed in a corresponding proportion, and then filled into the vinyl triethoxysilane modified reduced graphene oxide aerogel by a vacuum assisted infusion process, and finally the vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite material is obtained by vacuum room temperature curing molding.

[0030] The present invention has the following beneficial effects:

[0031] 1. In the composite process of carbon aerogel and silicone rubber, silane coupling agents such as vinyl triethoxysilane are used to modify the surface of carbon aerogel. The successful introduction of silane coupling agents such as vinyl triethoxysilane improves the crosslinking degree of the composite material, optimizes the interface compatibility between carbon aerogel and silicone rubber, and improves the matching degree between the two, thereby effectively improving the tensile strength of the composite material; secondly, the introduction of vinyl-terminated methyl silicone resin (VMQ) and high-viscosity vinyl-terminated polydimethylsiloxane (1900-2200mPa·s PDMS), a co-crosslinking system of vinyl-terminated polydimethylsiloxane (PDMS) and vinyl-terminated methyl silicone resin (VMQ) can be obtained through a hydrosilylation reaction. Based on the unique large-size cage structure of vinyl-terminated methyl silicone resin and the longer molecular chain of high-viscosity vinyl-terminated polydimethylsiloxane, the carbon aerogel modified by vinyl triethoxysilane and the co-crosslinking silicone system are combined into an interpenetrating network with "button-type" interpenetrating network crosslinking points, thereby further enhancing the matching compatibility between the carbon aerogel network and the silicone rubber network, so that the composite material finally obtains ultra-high (up to 1792.78) and adjustable (ranging from 3.29 to 1792.78) strain sensitivity (Gauge Factor), the ability to capture tiny strains (0.1%) and excellent resistance response stability.

[0032] 2. The silane coupling agent modified carbon aerogel / silicone rubber double network composite material provided by the present invention can achieve relatively excellent electrical conductivity with very little conductive filler addition. When the conductive filler addition amount is 0.487wt%, the conductivity of the composite material can reach 8.8496S / m. At the same conductive filler addition amount, the conductive performance of the composite material is better than that of carbon material conductive silicone rubber prepared by traditional blending process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is an inference diagram of the changes in the internal structure of the vinyltriethoxysilane-modified reduced graphene oxide aerogel / silicone rubber double network composite material in Example 1 (without adding 2000 mPa·s vinyl-terminated polydimethylsiloxane) during the stretching process from 0 to the strain corresponding to the modulus transition point.

[0034] Figure 2 This is an inference diagram of the changes in the internal structure of the vinyltriethoxysilane-modified reduced graphene oxide aerogel / silicone rubber double network composite material (with 2000 mPa·s vinyl-terminated polydimethylsiloxane added) in Example 2 during the stretching process from 0 to the strain corresponding to the modulus transition point. DETAILED DESCRIPTION

[0035] The principles, features and advantages of the present invention are further described in more detail below. The examples given are only used to explain the present invention but not to limit the scope of the present invention.

[0036] The raw materials and reagents used in the following examples are all commercially available products unless otherwise specified. Among them, vinyl-terminated polydimethylsiloxanes were purchased from Shandong Dayi Chemical Co., Ltd., with viscosities of about 500mPa·s and 2000mPa·s, respectively, and vinyl contents of 0.0141-0.0173mol / 100g and 0.0067-0.0135mol / 100g, respectively. Polydimethylsiloxane was purchased from Shandong Dayi Chemical Co., Ltd., and vinyl-terminated methyl silicone resin was purchased from Shandong Dayi Chemical Co., Ltd., with a vinyl content of 0.0404mol / 100g and a viscosity of about 2500mPa·s. Catalysts were purchased from Guangzhou Changsheng Chemical Co., Ltd.

[0037] Example 1 Effect of vinyl terminated methyl silicone resin (VMQ) on the internal structure and properties of vinyltriethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composites

[0038] When preparing the silicone rubber raw material solution, 100 parts of vinyl-terminated polydimethylsiloxane, an appropriate amount of crosslinking agent, 5 parts of polydimethylsiloxane, 0 parts or 30 parts of vinyl-terminated methyl silicone resin, 0.3 parts of inhibitor, 1.6 parts of Pt catalyst, and 10-30 parts of white carbon black are taken by weight, and the raw materials are evenly mixed to obtain a silicone rubber raw material solution. The obtained silicone rubber raw material solution is impregnated into the vinyl triethoxysilane modified reduced graphene oxide aerogel by a vacuum-assisted impregnation process. The results show that a maximum of 20 parts of white carbon black can be added to the silicone rubber raw material solution without the introduction of vinyl-terminated methyl silicone resin, and the increase of white carbon black cannot be fully impregnated into the vinyl triethoxysilane modified reduced graphene oxide aerogel, while a double network composite material with 30 parts of vinyl-terminated methyl silicone resin can add a maximum of 30 parts of white carbon black. This makes the composite material with the addition of vinyl-terminated methyl silicone resin effectively improve its own crosslinking degree while ensuring the tensile strength.

[0039] The preparation of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite material comprises the following steps:

[0040] 1. Preparation of reduced graphene oxide aerogel

[0041] 1.1 Preparation of dispersion:

[0042] 12 ml of graphene oxide (GO) aqueous dispersion, 1.5 ml of sodium dodecyl sulfate (SDS) aqueous solution (concentration: 50 mg / ml), and 264 mg of L-ascorbic acid are mixed uniformly to obtain a mixed solution; wherein the graphene oxide has a sheet diameter of 10-20 μm, a sheet thickness of about 1 nm, a layer number of 1-5, a carbon content of less than 46%, an oxygen content of greater than 46%, and the concentration of the graphene oxide aqueous dispersion is 11 mg / ml.

[0043] 1.2 In-situ foaming:

[0044] The mixed solution was magnetically stirred to make it foam, the stirring rate of the magnetic stirrer was 2100 r / min, and the stirring time was 5 min.

[0045] 1.3 Two-step hydrothermal reduction, freeze-thaw, water washing, solvent replacement, room temperature and pressure drying and post-treatment:

[0046] The foamed sample was kept at 75°C for 1 hour for partial hydrothermal reduction; the sample was then placed in a freezer and frozen at -18°C for 2 hours, and then thawed at room temperature; after thawing, it was kept at 90°C for 6 hours for complete hydrothermal reduction; the obtained sample was then washed with 830 times the mass of deionized water, and then the sample was replaced with 830 times the mass of anhydrous ethanol for 1 hour, and after filtering to remove the ethanol, the sample was replaced 4 times in the same way; the replaced sample was placed in a blast drying oven and dried at 60°C for 24 hours, and then the dried sample was placed in a tubular furnace, heated to 400°C in a nitrogen atmosphere, and calcined at this temperature for 2 hours to obtain reduced graphene oxide aerogel.

[0047] The cross-section and longitudinal sections of the obtained reduced graphene oxide aerogel were photographed using a scanning electron microscope. From the cross-section, the distribution of the pores is dense, and large-diameter pores with a pore size of about 50-300 μm and ultra-large pores with a pore size of about 800 μm appear. From the longitudinal section, pores with a pore size equivalent to that of the cross-section also appear (large pore diameter: 50-300 μm, ultra-large pore diameter: 500-1200 μm).

[0048] The density of the obtained reduced graphene oxide aerogel was tested and its density was 0.006 g / cm 3 .

[0049] 2. Modification of reduced graphene oxide aerogel

[0050] Vinyltriethoxysilane is prepared into a 5wt% solution with anhydrous ethanol, and the reduced graphene oxide aerogel prepared in step 1 is completely immersed in the solution. After soaking for 11 hours, it is taken out and dried in a forced air drying oven at 60°C for 24 hours to obtain vinyltriethoxysilane-modified reduced graphene oxide aerogel.

[0051] 3. Composite of vinyltriethoxysilane modified reduced graphene oxide aerogel and silicone rubber

[0052] 3.1 Preparation of silicone rubber raw material solution:

[0053] In parts by weight, 100 parts of vinyl-terminated polydimethylsiloxane, 20 parts of white carbon black, an appropriate amount of a crosslinking agent, 5 parts of polydimethylsiloxane, 0 parts of a vinyl-terminated methyl silicone resin, 0.3 parts of an inhibitor, and 1.6 parts of a Pt catalyst are taken and mixed uniformly to obtain a silicone rubber raw material solution 1.

[0054] In parts by weight, 100 parts of vinyl-terminated polydimethylsiloxane, 30 parts of white carbon black, an appropriate amount of a crosslinking agent, 5 parts of polydimethylsiloxane, 30 parts of vinyl-terminated methyl silicone resin, 0.3 parts of an inhibitor, and 1.6 parts of a Pt catalyst are taken, and the raw materials are mixed evenly to obtain a silicone rubber raw material solution 2.

[0055] In silicone rubber raw material solutions 1 and 2, the viscosity of vinyl-terminated polydimethylsiloxane is 500mPa·s, and the vinyl content is 0.0141-0.0173mol / 100g; the viscosity of polydimethylsiloxane is 500mPa·s; the vinyl content of vinyl-terminated methyl silicone resin is 0.0404mol / 100g, and the viscosity is about 2500mPa·s; the inhibitor is 5wt% acetylene cyclohexanol solution, the solvent is polydimethylsiloxane with a viscosity of 500mPa·s; the Pt catalyst is a platinum complex of tetramethyldivinylsiloxane; the cross-linking agent is hydrogen-containing silicone oil, the hydrogen content is 0.8wt%, and it is added according to the standard that the molar ratio of carbon-carbon double bonds in vinyl-terminated polydimethylsiloxane and vinyl-terminated methyl silicone resin to silicon-hydrogen bonds in hydrogen-containing silicone oil is 1:1.2.

[0056] 3.2 Preparation of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite material: Slowly pour the fully mixed silicone rubber raw material solution 1 and silicone rubber raw material solution 2 into the beaker containing vinyl triethoxysilane modified reduced graphene oxide aerogel, so that the liquid level exceeds the upper surface of the aerogel by about 2 mm, and adjust the position of the aerogel in the silicone rubber raw material solution by a glass rod so that it is in the middle of the beaker. Then put the beaker into a vacuum drying oven, and use the vacuum environment (vacuum degree 0.1Mpa) to assist the silicone rubber raw material solution to be fully immersed in the aerogel. During this period, it is necessary to unload the vacuum every 15 minutes, restore it to normal pressure, and then re-evacuate it. Repeat this operation several times until the silicone rubber raw material solution no longer produces bubbles in the vacuum environment (vacuum degree 0.1Mpa). After completing the above operations, there is no need to take out the beaker, and the temperature of the vacuum drying oven is directly set to 60°C to cure it in a vacuum environment (vacuum degree 0.1 MPa) for 12 hours. Finally, two types of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite materials with and without the addition of vinyl terminated methyl silicone resin are prepared.

[0057] The two vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composites prepared above were subjected to tensile tests using an electronic universal testing machine, and it was found that the stress-strain curve of the composite material introduced with 30 parts of vinyl terminated methyl silicone resin showed an obvious Young's modulus transition point (43%) compared with the stress-strain curve of the composite material without the introduction of vinyl terminated methyl silicone resin, which also indicates the formation of an interpenetrating network with "button-type" interpenetrating network cross-linking points inside the composite material. The schematic diagram of the interpenetrating network with "button-type" interpenetrating network cross-linking points is shown in FIG. Figure 1 shown.

[0058] The electrical conductivity of the two vinyltriethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composites prepared above was tested using a four-probe resistance tester. The conductivity of the composite material introduced with 30 parts of vinyl-terminated methyl silicone resin was 8.85S / m, and the conductivity of the composite material without the introduction of vinyl-terminated methyl silicone resin was 8.83S / m. The conductivity did not change significantly, which indicates that the introduction of vinyl-terminated methyl silicone resin will not destroy the original conductive network of the reduced graphene oxide aerogel.

[0059] After calculation, in the composite material introduced with 30 parts of vinyl-terminated methyl silicone resin, the proportion of vinyl triethoxysilane modified reduced graphene oxide aerogel is only 0.487wt%, which shows that the composite material of the present invention can achieve excellent conductive properties with only a small amount of conductive filler. Under the same amount of conductive filler added, the conductive properties of the composite material of the present invention are better than those of carbon material conductive silicone rubber prepared by traditional blending process. Example 2 Effect of high viscosity polydimethylsiloxane (2000mPa·s PDMS) on the internal structure and properties of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite material

[0060] The preparation of vinyltriethoxysilane modified dual template reduced graphene oxide aerogel / silicone rubber composite material comprises the following steps:

[0061] 1. Preparation of reduced graphene oxide aerogel

[0062] According to the operation in step 1 of Example 1, reduced graphene oxide aerogel was prepared.

[0063] 2. Modification of reduced graphene oxide aerogel

[0064] According to the operation in step 2 of Example 1, vinyltriethoxysilane-modified reduced graphene oxide aerogel was prepared.

[0065] 3. Composite of vinyltriethoxysilane modified reduced graphene oxide aerogel and silicone rubber

[0066] 3.1 Preparation of silicone rubber raw material solution: by weight, take 100 parts of vinyl-terminated polydimethylsiloxane, 30 parts of white carbon black, an appropriate amount of crosslinking agent, 5 parts of polydimethylsiloxane, 30 parts of vinyl-terminated methyl silicone resin, 0.3 parts of inhibitor, and 1.6 parts of Pt catalyst, mix the raw materials evenly to obtain a silicone rubber raw material solution.

[0067] Among them, the vinyl-terminated polydimethylsiloxane contains two components with viscosities of 2000mPa·s and 500mPa·s, respectively. The mass ratios of the 2000mPa·s product and the 500mPa·s product are 0 (indicating that the product does not contain 2000mPa·s), 1:5, and 1:2, respectively. The vinyl content of the vinyl-terminated polydimethylsiloxane with a viscosity of 500mPa·s is 0.0141-0.0173mol / 100g, and the vinyl content of the vinyl-terminated polydimethylsiloxane with a viscosity of 2000mPa·s is 0.0067-0.0135mol / 100g. The viscosity of polydimethylsiloxane is 500mPa·s. The vinyl content of the vinyl-terminated methyl silicone resin is 0.0404mol / 100g, and the viscosity is about 2500mPa·s. The inhibitor is a 5wt% acetylene cyclohexanol solution, and the solvent is polydimethylsiloxane with a viscosity of 500mPa·s. The Pt catalyst is a platinum complex of tetramethyl divinylsiloxane. The crosslinking agent is hydrogen-containing silicone oil with a hydrogen content of 0.8wt%, which is added according to the standard of 1:1.2 molar ratio of carbon-carbon double bonds in vinyl-terminated polydimethylsiloxane and vinyl-terminated methyl silicone resin to silicon-hydrogen bonds in hydrogen-containing silicone oil.

[0068] 3.2 Preparation of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite materials: According to the operation in step 3.2 of Example 1, three types of vinyl triethoxysilane modified reduced graphene oxide aerogel / silicone rubber double network composite materials were finally prepared.

[0069] The three composite materials were tensile tested using an electronic universal testing machine. The results showed that as the proportion of vinyl-terminated polydimethylsiloxane with a viscosity of 2000 mPa·s increased, the strain value corresponding to the transition point of Young's modulus decreased. The test results are shown in Table 1.

[0070] Table 1

[0071]

[0072] The crosslinking density of the three silicone rubbers, the crosslinking density of the three composite materials, and the crosslinking density ratio of the three composite materials to their corresponding silicone rubber were tested by low-field nuclear magnetic resonance. The test selected the XLD2 fitting method, the test temperature was 35°C, the sample density was set to 1g / ml, and the average value was taken after 4 repetitions. The test results are shown in Table 2.

[0073] Table 2

[0074]

[0075] It can be seen from the table that with the increase of the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane, the cross-linking density of the composite material shows a trend of first increasing and then decreasing. Among them, when the mass proportion is 1:5, the cross-linking density of the composite material is the highest. It can also be seen from Table 1 that the composite material under this ratio has the highest tensile strength and elongation at break. However, when the mass proportion is 1:2, the cross-linking density of the composite material decreases to a certain extent, and its tensile strength and elongation at break also decrease. The reason is that the vinyl content of 2000mPa·s vinyl-terminated polydimethylsiloxane (0.0091mol / 100g) is lower than the vinyl content of 500mPa·s vinyl-terminated polydimethylsiloxane (0.0153mol / 100g). As the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane continues to increase, the cross-linking density of the composite material begins to decrease, which also affects the mechanical properties of the composite material. From the crosslinking density ratios of the three composite materials and their corresponding silicone rubbers in Table 2, it can be seen that with the increase in the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane, the crosslinking density ratio of the composite material and its corresponding silicone rubber increases and gradually tends to 1, that is, the crosslinking degree of the composite material gradually approaches the crosslinking degree of its corresponding silicone rubber, indicating that increasing the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane can effectively improve the matching compatibility between the reduced graphene oxide aerogel network and the silicone rubber network, so that the crosslinking degree of the interpenetrating network composed of two networks with large scale differences is basically close to the crosslinking degree of a single silicone rubber polymer network. The internal structure diagram of the composite material is shown in Figure 2 .

[0076] The electrical conductivity of the three composite materials was tested using a four-probe resistance tester, and the conductivities were 8.8512 S / m, 8.8496 S / m and 8.7984 S / m, respectively. It can be seen that the conductivity values ​​of the three composite materials are basically the same, indicating that increasing the proportion of 2000 mPa·s vinyl-terminated polydimethylsiloxane will basically not affect the conductivity of the composite material, that is, the addition of 2000 mPa·s vinyl-terminated polydimethylsiloxane will not affect the structural integrity of the conductive network inside the composite material.

[0077] The tensile resistance response performance of the three composite materials was tested using an electronic universal testing machine and a digital multimeter. The strain sensitivity (Gauge Factor, GF) can be expressed as the ratio of the relative change of resistance R to mechanical strain ε: GF·ε=(R i -R0) / R0, where R0, Ri Represent the resistance of the sample before and after the load is applied, (R i -R0) / R0 represents the resistance change rate, and ε represents the strain of the sample. The resistance change rate-strain curves of the three composite materials were fitted with an exponential function, and the strain sensitivity of the three composite materials was obtained by differential calculation. The calculation results are shown in Table 3. It can be seen that with the increase in the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane, the strain sensitivity of the composite material increased sharply, which once again shows that increasing the proportion of 2000mPa·s vinyl-terminated polydimethylsiloxane can effectively improve the matching compatibility between the reduced graphene oxide aerogel network and the silicone rubber network.

[0078] Table 3

[0079]

[0080] An electronic universal testing machine and a digital multimeter were used to test the resistance response of a composite material with a mass ratio of 1:5 between vinyl-terminated polydimethylsiloxane with a viscosity of 2000mPa·s and vinyl-terminated polydimethylsiloxane with a viscosity of 500mPa·s to a small strain (0.1%). The results showed that when the strain was 0.1%, the composite material could still detect a certain degree of resistance response, and the resistance change rate was about 1.5%.

[0081] An electronic universal testing machine and a digital multimeter were used to test the cyclic tensile resistance response stability of a composite material with a mass ratio of 1:5 between vinyl-terminated polydimethylsiloxane with a viscosity of 2000mPa·s and vinyl-terminated polydimethylsiloxane with a viscosity of 500mPa·s (strain of 30% and number of cycles of 500). The results showed that the composite material can maintain its resistance change rate basically unchanged during the cyclic stretching process, which indicates that the composite material has excellent resistance response stability and repeatability.

Claims

1. A method for preparing a silane coupling agent modified carbon aerogel / silicone rubber double network composite material, characterized in that The following steps are involved: (1) Using carbon materials to prepare carbon aerogel; (2) Surface modification of carbon aerogel using silane coupling agent; (3) Using modified carbon aerogel as a conductive filler, a vacuum-assisted infusion process is used to fill the silicone rubber raw material solution into the modified carbon aerogel, and then a vacuum curing molding process is performed to obtain a silane coupling agent modified carbon aerogel / silicone rubber double network composite material.

2. The preparation method according to claim 1, characterized in that: The carbon material used to prepare the carbon aerogel includes graphene oxide, carbon nanotubes, carbon fibers, cellulose, resorcinol, formaldehyde, melamine, phenol, furfural or cresol; preferably, the carbon material is graphene oxide.

3. The preparation method according to claim 1 or 2, characterized in that: The method used to prepare the carbon aerogel is selected from the sol-gel method, the hydrothermal method, the chemical vapor deposition method, the bubble template method, the ice template method, or a combination of two or more of these methods; preferably, the method used to prepare the carbon aerogel is a method combining the bubble template method and the ice template method.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The method of using a silane coupling agent to modify the surface of a carbon aerogel is as follows: the carbon aerogel is immersed in a mixed solution of the silane coupling agent and an organic solvent, and then dried to obtain a silane coupling agent-modified carbon aerogel.

5. The preparation method according to claim 4, characterized in that: Including at least one of the following conditions: Condition 1: The silane coupling agent includes vinyl triethoxysilane, vinyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane or aniline methyl triethoxysilane, preferably, the silane coupling agent is vinyl triethoxysilane; Condition 2: In the mixed solution of the silane coupling agent and the organic solvent, the concentration of the silane coupling agent is 3-9wt%; Condition 3: Soaking is carried out at room temperature for 10-12 hours; Condition 4: Drying is carried out at 55-65°C and the drying time is 24-26 hours.

6. The preparation method according to claim 1, characterized in that: During vacuum-assisted impregnation, the vacuum degree is 0.05-0.1Mpa; during vacuum curing molding, the vacuum degree is 0.05-0.1Mpa and the temperature is 55-65°C.

7. The preparation method according to claim 1, characterized in that The silicone rubber raw material solution is composed of 100 parts by weight of vinyl-terminated polydimethylsiloxane, 0-50 parts of white carbon black, 4-6 parts of polydimethylsiloxane, 0-50 parts of vinyl-terminated methyl silicone resin, 0.2-0.4 parts of inhibitor, 1.5-2 parts of Pt catalyst and cross-linking agent, wherein the amount of the cross-linking agent added is determined according to the standard that the molar ratio of carbon-carbon double bonds in vinyl-terminated polydimethylsiloxane and vinyl-terminated methyl silicone resin to silicon-hydrogen bonds in hydrogen-containing silicone oil is 1:1.1-1.

3.

8. The preparation method according to claim 7, characterized in that: The vinyl-terminated polydimethylsiloxane is selected from at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2200 mPa·s and a vinyl content of 0.0067-0.0135 mol / 100 g and a vinyl-terminated polydimethylsiloxane having a viscosity of 480-520 mPa·s and a vinyl content of 0.0141-0.0173 mol / 100 g; preferably, the content of the vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2200 mPa·s is 0-35%, more preferably 10-35%.

9. The preparation method according to claim 8, characterized in that: Including at least one of the following conditions: Condition 1: The viscosity of polydimethylsiloxane is 480-520 mPa·s; Condition 2: The vinyl content of the vinyl-terminated methyl silicone resin is 0.03-0.05 mol / 100 g and the viscosity is 2300-2600 mPa·s; Condition 3: The crosslinking agent is hydrogen-containing silicone oil, and the hydrogen content is 0.8wt%; Condition 4: the inhibitor is a 4-6 wt% acetylene cyclohexanol solution, and the solvent is polydimethylsiloxane with a viscosity of 480-520 mPa·s; Condition 5: The Pt catalyst is a platinum complex of tetramethyldivinylsiloxane.

10. A product obtained by the method for preparing a silane coupling agent modified carbon aerogel / silicone rubber double network composite material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of conductive silicone rubber composite material

    CN115010964A

  • Electromagnetic shielding silicon rubber / graphene / carbon nanotube nano composite material and preparation method thereof

    CN108165019A

  • Liquid silicone rubber / graphene aerogel highly conductive composite material and preparation method thereof

    CN110408217A

  • Graphene oxide aerogel-based electromagnetic shielding polymer composite material with electric conduction-thermal conduction dual-network structure and preparation method thereof

    CN112876848A

  • Low-thermal-resistance and high-thermal-conductivity graphene silicone rubber composite material and preparation method thereof

    CN114085530A